ANALISIS PERUBAHAN LUAS HUTAN MANGROVE MENGGUNAKAN METODE NDVI (NORMALIZED DIFFERENCE INDEX) DI KECAMATAN BALIKPAPAN BARAT KOTA BALIKPAPAN - Sahdian, Iitra Achbar; Keliwar, Khairi Ahza Hail; Luthfi Saud, Muhammad Nur Ibnu; Al Hakim, Muhammad Abdul Ghofur; Nugroho, Bayu Ashari; Kholifah, Puspa Indah Nur; Safitri, Rosita Dewi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Mangrove ecosystems are a crucial component of coastal areas, serving both strategic ecological and economic functions; however, their existence is vulnerable to human activities and the dynamics of coastal environments. The Balikpapan Barat subdistrict is one of the areas in Balikpapan City that features various types of activities, including settlements, industrial activities, and port activities, which have the potential to impact the condition of the mangrove forests. This study aims to analyse changes in the area and density of mangrove forests in 2019 and 2025 using the Normalised Difference Vegetation Index (NDVI) method based on Sentinel-2A satellite imagery. The research method comprises three stages: image pre-processing, NDVI value calculation, and classification of mangrove density into three classes: low, medium, and high. The analysis results indicate a decline in the distribution area of mangroves in West Balikpapan District, primarily due to anthropogenic activities such as infrastructure development, settlement expansion, and coastal industrial activities. However, some areas still exhibit moderate to high vegetation density, indicating the presence of natural regeneration processes and the role of conservation areas in maintaining mangrove ecosystems. This study confirms that the use of remote sensing imagery and the NDVI method is effective in supporting spatial and sustainable mangrove monitoring, and can serve as a basis for planning the management and conservation of mangrove ecosystems in coastal areas.Keywords: mangrove, NDVI, Sentinel-2, Area, Density, West Balikpapan.